REALISASI FONOLOGIS BUNYI BAHASA INDONESIA DALAM TUTURAN PENUTUR: ANALISIS SISTEM PELAFALAN - Rahma Indah Lestari; Putri Bella Sari; Silvina Noviyanti; Eka Artaulina S; Keisya Octa Fitri Dean; Endi Citra Pamungkas (Universitas Nias Raya, 2026)
This study aims to analyze the phonological realization of Indonesian language sounds in speakers' speech and to identify the factors influencing the pronunciation system. The study employs a descriptive qualitative approach using library research methods and content analysis techniques. The findings indicate that phonological realization in speakers' speech is dynamic and varied, influenced by the first language which consistently shapes articulatory patterns. Pronunciation variations manifest in the form of phoneme substitution, sound deletion, sound structure simplification, as well as differences in intonation and word stress. From a phonological perspective, such variation is part of a natural linguistic adaptation process that occurs in multilingual communities, rather than merely a language error. Furthermore, phonological realization has significant implications for communication effectiveness and Indonesian language learning. An understanding of phonological variation is expected to assist educators in designing more contextual and effective learning strategies for students with diverse regional language backgrounds.